Development of Bilingual Mathematics Digital Pocket Book to Improve Student’s Ability in Understanding Plane Topic - Nadya Ramadhani; Rahman Pratama Hasibuan (International Journal of Educational and Psychological Sciences, 2023)
The aim of this study was to develop a valid, practical, and effective bilingual mathematics digital pocket book to improve students’ ability in understanding plane topic. The study was held at SMP Islam Al-Ulum Terpadu Medan. The subject of this research was class VII-A. This study was a research and development (R&D) study using the ADDIE Model. The data collection technique used a questionnaire sheet for the assessment of material experts, teaching materials experts, learning practitioners and student responses. The results showed that the bilingual mathematics digital pocket book in plane topic obtained an average percentage of 93.18% with the criteria "very valid" by the assessment of material experts and teaching materials experts, obtaining an average percentage of 94.5% with the criteria of "very practical" by the assessment. learning practitioners, and obtained an average percentage of 86.72%. with the criteria of "very effective" by student assessment. Bilingual mathematics digital pocket book in plane topic that has been developed in this study was also considered "effective" if it was seen that the post-test scores reached 90% compared to the pre-test scores which reached 56%. Thus, based on the results of the assessment of material experts, teaching material experts, learning practitioners, and students, it can be said that the bilingual mathematics digital pocket book in plane topic has been tested to be valid, practical and effective for use in learning.